2023
DOI: 10.1002/ange.202310945
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Dimensional MFI‐Type Zeolite Flow Battery Membranes

Dezhu Zhang,
Kang Huang,
Yongsheng Xia
et al.

Abstract: Vanadium flow battery (VFB) is one of the most reliable stationary electrochemical energy‐storage technologies, and a membrane with high vanadium resistance and proton conductivity is essential for manufacturing high‐performance VFBs. In this study, a two‐dimensional (2D) MFI‐type zeolite membrane was fabricated from zeolite nanosheet modules, which displayed excellent vanadium resistance (0.07 mmol L‐1 h‐1) and proton conductivity (0.16 S cm‐1), yielding a coulombic efficiency of 93.9%, a voltage efficiency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
(2 reference statements)
0
0
0
Order By: Relevance
“…Since the semipermeable membrane is used in separating the positive and negative electrolytes of RFB, crossover problems have consistently been a significant challenge. The crossover of active species (metallic ion) used to be a challenge in all-iron RFB systems. To overcome the easy crossover issue of single ions, metal-ligand complexes instead of metal ions are suggested as active materials . Some studies have indicated that the crossover of large-volume metal-ligand complexes is negligible, which uses the Donnan effect and the size exclusion effect. , However, our previous research has revealed that the crossover of free ligands from the negative electrolyte poses another challenging problem .…”
mentioning
confidence: 99%
“…Since the semipermeable membrane is used in separating the positive and negative electrolytes of RFB, crossover problems have consistently been a significant challenge. The crossover of active species (metallic ion) used to be a challenge in all-iron RFB systems. To overcome the easy crossover issue of single ions, metal-ligand complexes instead of metal ions are suggested as active materials . Some studies have indicated that the crossover of large-volume metal-ligand complexes is negligible, which uses the Donnan effect and the size exclusion effect. , However, our previous research has revealed that the crossover of free ligands from the negative electrolyte poses another challenging problem .…”
mentioning
confidence: 99%